Preliminary exergy analysis of static flash of pure water. (July 2015) - Zhang, Dan; Yan, Junjie; Liu, Yingwen; Zhao, BingChao
Abstract: The waterfilm was selected as control volume and exergy transfer within it during static flash of pure water at different flash speeds was analyzed. Exergy balance during differential time was set up and exergy destruction was also deduced. It suggested that static flash was an irreversible process and boiling temperature difference ( BTD ) played a major role for exergy destruction. In order to measure the effectiveness of static flash on exergy transfer during entire flash duration time, exergy efficiency of flash ( EE ) was introduced as the fraction of the delivered exergy to the total released exergy from unit mass of initial waterfilm. Exergy efficiency of flash steam ( EEstm ) was defined as the fraction of exergy contained in latent heat of flash steam to the total released exergy from unit mass of initial waterfilm. Both efficiencies were evaluated and analyzed according to our former experimental results with initial temperature ranging between 46.5 and 104.6 °C, superheat between 1.78 and 43.9 K, initial height of waterfilm between 0.10 and 0.30 m, flash speed between 4.8 × 10 −4 and 2.18 s −1 . Results suggested that, first, EE varies between 0.86 and 0.99, and EEstm varied between 0.037 and 0.99 in current experimental range. Second EEstm could be improved by increasing initial temperature of waterfilm while at the same time reducing superheat, or initial height of waterfilm, or flash speed. At last, on basis of an empirical formula for BTD fitted from experimental results, a pair of calculation formulae for EE and EEstm were set up within acceptable error range.